Design of pico-hydro turbine generator systems for self-powered electrochemical water disinfection devices. (August 2018) - Powell, D.; Ebrahimi, A.; Nourbakhsh, S.; Meshkahaldini, M.; Bilton, A.M.
Abstract: Previous research has demonstrated the potential of pico-hydro turbines to provide reliable electricity in applications such as rural electrification. However, the literature has primarily focused on the development of turbine systems for design environments where spatial and flow rate constraints tend to be non-restrictive. The work detailed in this paper presents the development of a novel, compact, high efficiency turbine capable of powering a compact electrochemical cell for off-grid water disinfection. The turbine with the generator is capable of generating nearly 100 W of power with a footprint of only 8″ in length and 4″ in diameter. A basic mathematical model of a DC generator is coupled to a computational fluid dynamics (CFD) turbine model to evaluate different system configurations. Following a Taguchi Method study to computationally explore the turbine design space, experimental testing of improved turbine configurations is shown to provide electrical power output improvements of 20%. Selection of a more compatible DC generator also provides electrical power output and efficiency improvements of a factor of 2 and 2.5 respectively. Highlights: Design study of a novel pico-hydro turbine for a low flow application was conducted. Suitable generator pairing resulted in a factor of 2 improvement in power output. Taguchi method discretization of the turbine design space was performed. CFD analysis of turbine configurations used to assess effects of multiple parameters. Refined turbine design provided an improvement in power output of 20%.